A FRAMEWORK FOR INVESTIGATING THE INFLUENCE OF SOCIAL CONTEXT ON - Dixon, Sugnét (My University, 2011)
Presently very little is known about techniques and tools available and effective during a process of strategising. Partly the problems reside in the normally macro level approach taken during investigations into strategising. A study aimed at determining how to facilitate strategic session requires investigation into factor influencing the micro activity level where little theoretical knowledge exists. Understanding the practical activity level also requires building links between the micro and macro level. A micro approach must also acknowledge the importance of the macro context. This research will establish a framework for investigating the process of strategising, with the aim of investigating the influence of social context on the process of strategising at a micro level. A theoretical approach is utilised, adopting a framework based on the synthesising of activity theory and structurational theory. The applicability of Activity Theory as a framework is established in that it crosses the divide between the macro and micro level while being objective orientated. The importance of social context as a mediator connecting individuals during a strategising session is established. Such framework could be utilised to enhance the understanding and therefore the success of strategising for most organisational processes within both the corporate and governmental environment.
MBA - WBS
Keywords: Activity theory; Strategic planning